From colorless to pink: Structural insights into vitamin B12-induced color change in monoclonal antibodies - Kai-feng He; Hao-dong Cui; Wen-hui Deng; Na Xing; Guo-jian Liu; Abdallah Iddy Chaurembo; Li-dan Fu; Yuan Li; Xin-yue Tong; Han-bin Lin; Chun-he Wang (Medicine in Drug Discovery)
Background: Monoclonal antibodies (mAbs) are typically colorless; however, the pink coloration observed during production raises quality concerns. This study investigated the mechanism linking this color change to Vitamin B12 (VB12), which converts to hydroxycobalamin (OH-Cbl) under light and binds covalently to cysteine residues in antibodies via cobalt-sulfur bonds. Methods: Three batches of IgG1 antibodies (SP1, SP2, and NL)—were expressed in CHO cells, exposed to light, and purified. Binding interactions were analyzed using HPLC, RP-UPLC/MS, SDS-PAGE, and hydrophobic interaction chromatography (HIC). Peptide mapping and 3D structural modeling using protenix and autodock vina software identified the binding sites and spatial requirements. Results: OH-Cbl covalently binds to five cysteine residues: L_Csy138 and L_Csy218 (light chain) and H_Csy22, H_Csy96, and H_Csy323 (heavy chain). SP2 exhibited a higher VB12 content (molar ratio 1:5.71 vs. 1:9.74 in SP1) and increased hydrophobicity, confirming covalent attachment. Structural modeling revealed large protein pockets around these cysteines, accommodating VB12′s bulky structure. Peptide analysis revealed distinct UV absorption at 360 nm for SP2, while SDS-PAGE indicated slight molecular weight differences. Conclusion: The pink coloration arises from the light-induced conversion of VB12 to OH-Cbl, which binds covalently to specific cysteine residues, facilitated by spatially permissive protein pockets. Controlling the light exposure during production can mitigate this phenomenon. This study elucidates the structural basis of antibody-VB12 interactions, offering critical insights for optimizing mAb quality control.